Implementasi Kepemimpinan Guru PAI di SMPIT Ar-Raihan terhadap Pengembangan Karakteristik Peserta Didik - Lutfiana, Annisa; Mutiara, Elvian; Putri, Hesti Klatina; Nurhidayati, Risqina Putri (ARZUSIN, 2022)
Humans are essentially creatures who cannot live without the help of others. All activities and activities carried out must have interference from outside parties. School, is a place that has many goals and togetherness with the wider community. Teachers become second parents at school. all that is conveyed orally, exemplified from behavior and habits. The author wants to make observations to an Integrated Islamic school at SMPIT Ar-Raihan Bantul about the relationship between teacher exemplary as a leader and role model in an effort to develop the characteristics of students. The research design used descriptive qualitative analysis, observation as a data collection technique. In the leadership carried out by the Prophet Muhammad, there have been many steps that have been taken by him as this has become a direct example and role model for his followers. As a religious leader, the Prophet has exemplified the attitude of a true leader. The teacher must have a personality of character. The term that is often used in the world of education is integrity. Regarding the implementation of the role model strategy to build the characteristics of students, it was also carried out at the SMPIT Ar Raihan school as explained by Mr. Damhuri Batubara S.Pd.I, namely, by making the teacher himself a good role model or role model for students and instilling values. Islamic values.